Extracting Lessons on Gender in the Oil and Gas Sector : A Survey and Analysis of the Gendered Impacts of Onshore Oil and Gas Production in Three Developing Countries - Scott, Jen; Dakin, Rose; Heller, Katherine; Eftimie, Adriana (World Bank, Washington, DC, 2013)
The oil, gas, and mining unit series publishes reviews and analyses of sector experience from around the world as well as new findings from analytical work. It places particular emphasis on how the experience and knowledge gained relates to developing country policy makers, communities affected by extractive industries, extractive industry enterprises, and civil society organizations. This paper explores the divergent experiences of women and men who live in areas that are directly affected by oil and gas development, and highlights how the industry specifically contributes to 'gender gaps' in the unequal distribution of assets and risks. Evidence from surveys and interviews with community members, company representatives, and government an official in oil-and gas-affected areas is analyzed and potential solutions are presented to reduce inequality, increase operational efficiency, reduce risks, and foster sustainable development. The paper aims to demonstrate how oil companies, policy makers, and donors, as well as citizens and nonprofits, can benefit from facilitating more equitable sharing of oil and gas wealth, with a particular focus on the inclusion of women. It points out the gains that can be realized through mutual collaboration to minimize harm for those people whose lives and environments are most directly impacted by the industry. Gender, as defined here, is differentiated from biological sex: gender describes the separate behaviors, identities and roles into which males and females are socialized, and contrasts the freedoms and constraints that come with these roles. This paper therefore examines how gender influences risks and opportunities in upstream areas of oil-rich, low income countries. The paper adopts a qualitative approach to research, presenting the perspectives of the people who live in the immediate vicinity of upstream operations and attempting to faithfully interpret what can be learned from their testimonies.